Recognition of tRNAs with a long variable arm by aminoacyl-tRNA synthetases - Tukalo, M.A.; Yaremchuk, G.D.; Kovalenko, O.P.; Kriklivyi, I.A.; Gudzera, O.I. (Вiopolymers and Cell, 2013)
In prokaryotic cells three tRNA species, tRNASer, tRNALeu and tRNATyr, possess a long variable arm of 11–20 nucleotides (type 2 tRNA) rather than usual 4 or 5 nucleotides (type 1 tRNA). In this review we have summarized the results of our research on the structural basis for recognition and discrimination of type 2 tRNAs by Thermus thermophilus seryl-, tyrosyl- and leucyl-tRNA synthetases (SerRS, TyrRS and LeuRS) obtained by X-ray crystallography and chemical probing tRNA in solution. Crystal structures are now known of all three aminoacyl-tRNA synthetases complexed with type 2 tRNAs and the different modes of tRNA recognition represented by these structures will be discussed. In particular, emphasis will be given to the results on recognition of characteristic shape of type 2 tRNAs by cognate synthetases. In tRNASer, tRNATyr and tRNALeu the orientation of the long variable arm with respect to the body of the tRNA is different and is controlled by different packing of the core. In the case of SerRS the N-terminal domain and in the case of TyrRS, the C-terminal domain, bind to the characteristic long variable arm of the cognate RNA, thus recognizing the unique shape of the tRNA. The core of T. thermophilus tRNALeu has several layers of unusual base-pairs, which are revealed by the crystal structure of tRNALeu complexed with T. thermophilus LeuRS and by probing a ligand-free tRNA by specific chemical reagents in solution. In the crystal structure of the LeuRS-tRNALeu complex the unique D-stem structure is recognized by the C-terminal domain of LeuRS and these data are in good agreement with those obtained in solution. LeuRS has canonical class I mode of tRNA recognition, approaching the tRNA acceptor stem from the D-stem and minor groove of the acceptor stem side. SerRS also has canonical class II mode of tRNA recognition and approaches tRNASer from opposite, variable stem and major groove of acceptor stem site. And finally, TyrRS in strong contrast to canonical class I system has class II mode of tRNA recognition.